Comportamento mecânico de concretos de pós reativos submetidos a elevadas temperaturas - Soardi, Alessandro (2022)
Reactive powder concrete (RPC), the main representative of ultra high performance concrete (UHPC), is a material that has high compressive strength, high compactness and low fluid permeability. Such properties come from the use of high consumption of binders, extremely fine aggregates and a low water/binder ratio, combined with the use of superplasticizer additives from last generation. These characteristics make RPC a material with great potential for use in special constructions. However, its high compactness and low permeability also favor the occurrence of detachment of CPR layers during exposure to high temperatures. The detachment of concrete by the action of temperature is known as spalling effect and can occur explosively. Several studies have reported that this phenomenon usually occurs in high performance concrete (HPC), due to its low permeability, and this same behavior has been verified in RPC at certain temperatures. One of the measures to mitigate spalling in concrete is the incorporation of polypropylene fibers during the mixing of the material, in order to improve its behavior in fire situations. The present research evaluated the effect of temperatures of 200, 300, 400, 600 and 800 °C on the mechanical properties of RPC traces, at 91 days of curing, with water/cement factors corresponding to 0.18 and 0.21. It was also verified the influence of the incorporation of polypropylene fibers in the reduction of eventual damages caused by heating, in the contents of 0, 0.15 and 0.30% by volume. After cooling, tests of axial compressive strength, tensile strength by diametral compression and ultrasonic pulse velocity of the concrete were carried out, in addition to the mass variation of the samples. Through the experimental program, it was possible to verify the occurrence of explosive detachment of all samples of the traces without addition of fibers, at temperatures of 400, 600 and 800 °C, and that its intensity was higher for samples with lower w/c. The addition of 0.30% fiber proved to be satisfactory in mitigating spalling, while the addition of 0.15% did not completely inhibit the occurrence of the phenomenon. Also highlighted was the increase in axial compressive strength by up to 61% after exposure to a temperature of 300 °C, and maintenance of up to 61% of the initial strength, even when exposed to a temperature of 800 °C. It was possible to perceive that, for the RPC to minimally resist spalling and maintain considerable residual mechanical strength, the use of polypropylene fibers as passive protection is essential.